O-19 Research active hospices: the potential of people and partnerships. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Russell, Sarah; Hodson, Melanie
Abstract : Background: Supporting hospices to be research active is a strategic objective of Hospice UK following the publication of Research in palliative care: can hospices afford not to be involved? (Payne et al., 2013). Aims: To understand the needs, concerns and potential solutions from the hospice, academic, NHS research, clinical community and other stakeholders for hospices to be research active. Methods: November 2015 to February 2016 informal mapping was carried out with 34 stakeholders (data set 1). May to June 2016, two stakeholder meetings with 110 participants (data set 2) and a Survey Monkey questionnaire with over 100 responses (data set 3). May 2016 a #whywedoresearch Twitter chat on hospice research with @researchospice (data set 4). Results: Data driven thematic analysis of the four data sets reported in three domains (needs, concerns and potential solutions). The three domains were also set within a micro (individual), meso (team or organisational) and macro (regional or national) context. Conclusions: The four data sets harnessed the potential of people, teams' and organisations' expertise and passion. Partnership is the way forward to support hospices to be research active. Using the data sets, further consultation and research, the forthcoming Hospice UK action plan will propose the shared goals, timelines and outputs for hospices to be 'research active'. Funding: The project was funded by the employing organisation.